Customized reconstruction of alveolar cleft by high mechanically stable bioactive ceramic scaffolds fabricated by digital light processing. (June 2022) - Yin, Xiaohong; Li, Qi; Hong, Yirong; Yu, Xiaowen; Yang, Xianyan; Bao, Zhaonan; Yu, Mengfei; Yang, Huayong; Gou, Zhongru; Zhang, Bin
Graphical abstract: Highlights: Scaffold matching the shape of alveolar defect with micropores distributed in roof layer is designed. The strontium-doped α-tricalcium phosphate scaffolds exhibit excellent long-term mechanical stability. The strontium-doped α-tricalcium phosphate scaffolds possess expected biodegradation and osteogenic capability. Abstract: Due to the personalized large defect and bone absorption of the alveolar cleft, its regeneration is still a great challenge. Conventional autologous bone repair leads to donor site adverse reactions and then bioactive materials with stable mechanical properties, suitable degradation rates, good osteogenic ability are required. In this study, the α-tricalcium phosphate (doping with and without 6% strontium; α-TCP-Sr6, α-TCP) bioceramic scaffolds with high-precision pore structure were developed to repair the alveolar cleft, and the physicochemical properties and bone repair performances were systematically compared with the pure β phase of tricalcium phosphate (β-TCP) bioceramic scaffolds. It was shown that Sr dopant could adjust the bio-dissolution of α-TCP scaffolds, and contributed to excellent mechanical stability. As for the osteogenic capability in the alveolar cleft of rabbits, the α-phase TCP scaffolds both exhibited appreciable new bone ingrowth compared to the β-TCP scaffolds. However, bone malformation and fibrous tissue invasion occurred in the control group (without filling scaffolds). This study suggests that the Sr dopant may adjust the biodegradation and mechanical stability of α-TCP, and such biodegradable Ca-phosphate bioceramics scaffolds prepared by digital light processing (DLP)-based 3D printing technique demonstrate significance in promoting the reconstruction of the alveolar cleft.